Effects of social structure and management on risk of disease establishment in wild pigs. Issue 4 (9th January 2021) - Yang, Anni; Schlichting, Peter; Wight, Bethany; Anderson, Wesley M.; Chinn, Sarah M.; Wilber, Mark Q.; Miller, Ryan S.; Beasley, James C.; Boughton, Raoul K.; VerCauteren, Kurt C.; Wittemyer, George; Pepin, Kim M.
Abstract: Contact heterogeneity among hosts determines invasion and spreading dynamics of infectious disease, thus its characterization is essential for identifying effective disease control strategies. Yet, little is known about the factors shaping contact networks in many wildlife species and how wildlife management actions might affect contact networks. Wild pigs in North America are an invasive, socially structured species that pose a health concern for domestic swine given their ability to transmit numerous devastating diseases such as African swine fever (ASF). Using proximity loggers and GPS data from 48 wild pigs in Florida and South Carolina, USA, we employed a probabilistic framework to estimate weighted contact networks. We determined the effects of sex, social group and spatial distribution (monthly home‐range overlap and distance) on wild pig contact. We also estimated the impacts of management‐induced perturbations on contact and inferred their effects on ASF establishment in wild pigs with simulation. Social group membership was the primary factor influencing contacts. Between‐group contacts depended primarily on space use characteristics, with fewer contacts among groups separated by >2 km and no contacts among groups >4 km apart within a month. Modelling ASF dynamics on the contact network demonstrated that indirect contacts resulting from baiting (a typical method of attracting wild pigs or game species to a site to enhance recreational hunting) increased the risk of disease establishment by ~33% relative to direct contact. Low‐intensity population reduction (<5.9% of the population) had no detectable impact on contact structure but reduced predicted ASF establishment risk relative to no population reduction. We demonstrate an approach for understanding the relative role of spatial, social and individual‐level characteristics in shaping contact networks and predicting their effects on disease establishment risk, thus providing insight for optimizing disease control in spatially and socially structured wildlife species. Abstract : This article implemented a probabilistic approach to define weighted contact networks across two wild pig populations with two main features (contact probability and rate) to understand the effects of management processes on transmission of African Swine Fever, a disease of global concern.